2017
DOI: 10.1186/s13040-017-0139-3
|View full text |Cite
|
Sign up to set email alerts
|

Grid-based stochastic search for hierarchical gene-gene interactions in population-based genetic studies of common human diseases

Abstract: BackgroundLarge-scale genetic studies of common human diseases have focused almost exclusively on the independent main effects of single-nucleotide polymorphisms (SNPs) on disease susceptibility. These studies have had some success, but much of the genetic architecture of common disease remains unexplained. Attention is now turning to detecting SNPs that impact disease susceptibility in the context of other genetic factors and environmental exposures. These context-dependent genetic effects can manifest themse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…These variations were incorporated of a model that includes Crush, a stochastic search technique to explore relations between genes in genome-wide data as an application of multifactor dimensionality reduction (MDR). Applying the approach to an AZ GWAS dataset, results showed that Crush-MDR was capable of identifying a collection of interacting genes with biological linkages to Alzheimer's disease [57]. Xu et al employed a Time-Varying Group Sparse Additive Model (TV-GroupSpAM) to carry out a two-stage SNP selection.…”
Section: ) Machine Learning Methodsmentioning
confidence: 99%
“…These variations were incorporated of a model that includes Crush, a stochastic search technique to explore relations between genes in genome-wide data as an application of multifactor dimensionality reduction (MDR). Applying the approach to an AZ GWAS dataset, results showed that Crush-MDR was capable of identifying a collection of interacting genes with biological linkages to Alzheimer's disease [57]. Xu et al employed a Time-Varying Group Sparse Additive Model (TV-GroupSpAM) to carry out a two-stage SNP selection.…”
Section: ) Machine Learning Methodsmentioning
confidence: 99%
“…Epistatic interaction terms were selected using multifactor dimensionality reduction (MDR) [19], a nonparametric approach that collapses the genotype combinations into high risk or low risk, then tests this new variable's association with the phenotype using cross validation. The Crush-MDR algorithm [13] uses an evolutionary algorithm guided by expert knowledge to mine the space of SNP interactions. Candidate SNPs to include in the interaction mining were selected within each training set of unrelated individuals.…”
Section: Epistatic Interaction Feature Engineeringmentioning
confidence: 99%
“…Expert knowledge from databases (such as gene ontology) or literature sources (such as PubMed) was used to filter gene datasets before the analysis. They applied this method to the GWAS dataset from ADNI and identified a set of interacting genes related to AD [ 137 ].…”
Section: Gene-gene Interaction In Admentioning
confidence: 99%